2004
DOI: 10.1007/s00217-004-1025-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential for acrylamide formation in potatoes: data from the 2003 harvest

Abstract: Reducing sugars, free amino acids, and the potential for acrylamide formation were determined in more than 50 potato samples from the 2003 harvest in Switzerland. The reducing sugar content strongly correlated with acrylamide, whereas no correlation was found between acrylamide and free asparagine or the pool of free amino acids. The reducing sugar contents and the acrylamide potentials were higher in most of the cultivars tested than in the samples from 2002. This was probably due to the hot and dry summer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
92
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 28 publications
18
92
0
Order By: Relevance
“…The effects were likewise but less pronounced for the roasting experiment carried out at 130 C: reducing sugar decreased by more than 50%, whereas still 95% of the initial asparagine content was found. Similar behavior of these compounds was also observed in heated potatoes [24]. Glucose and fructose react much faster than free asparagine upon heating and therefore their content could directly influence acrylamide formation.…”
Section: Changes Of Sugar and Asparagine Content In Almonds During Rosupporting
confidence: 70%
See 1 more Smart Citation
“…The effects were likewise but less pronounced for the roasting experiment carried out at 130 C: reducing sugar decreased by more than 50%, whereas still 95% of the initial asparagine content was found. Similar behavior of these compounds was also observed in heated potatoes [24]. Glucose and fructose react much faster than free asparagine upon heating and therefore their content could directly influence acrylamide formation.…”
Section: Changes Of Sugar and Asparagine Content In Almonds During Rosupporting
confidence: 70%
“…On a molar basis free asparagine is roughly as abundant as the reducing sugars: The ratio of the molar content of free asparagine to reducing sugars ranged from 0.8 to 1.2. Thus, the situation of the acrylamide precursors in almonds is different from that for potatoes, where reducing sugars are limiting [9,23,24], or that for sweet bakery products, where asparagine is limiting [12,18]. As can be seen from the relative standard deviation, the reducing sugars varied somewhat more between the cultivars than free asparagine.…”
Section: Changes Of Sugar and Asparagine Content In Almonds During Romentioning
confidence: 94%
“…Amrein et al 9,21) and Becalski et al 19) reported that the correlation between levels of components in tubers and the acrylamide level in chips increased slightly when asparagine content was included with the reducing sugars. We analyzed our data using Amrein's formula, (0.5 Â glucose + fructose) Â asparagine, in which glucose is weighted at half of fructose based on their relative efficiencies in acrylamide formation.…”
Section: Analysis Of the Relationship Between Levels Of Tuber Componementioning
confidence: 99%
“…Third, we tried to clarify the relationship between tuber components and acrylamide formation in chips from the results of this study, which gave a wider concentration range than in previous studies. 9,[19][20][21][22] …”
mentioning
confidence: 99%
“…In the case of potato tubers, fructose and glucose account for almost all the reducing sugar content, with almost no maltose present. The relationship between precursor concentration and acrylamide formation in potato is complex, with reducing sugars being the major determinants of acrylamide-forming potential in most datasets but free asparagine contributing to the variance in some (Amrein et al 2003(Amrein et al , 2004Becalski et al 2004;De Wilde et al 2005;Elmore et al 2007Elmore et al , 2010Shepherd et al 2010;Halford et al 2012b;Muttucumaru et al 2013Muttucumaru et al , 2014. Free asparagine concentration has more influence in French fry rather than crisping varieties, probably because French fry varieties contain higher concentrations of sugars (Halford et al 2012b;Muttucumaru et al 2014), and modelling of the relationship between the ratio of free asparagine to reducing sugars in potatoes with unusually low concentrations of free asparagine from a U.K. field trial identified a ratio of free asparagine to reducing sugars of 2.257 ± 0.149 as a tipping point below which free asparagine concentration could affect acrylamide formation (Muttucumaru et al 2017).…”
Section: Introductionmentioning
confidence: 99%